Process for carburizing aluminum metal and the resulting aluminum-carbon alloy

CN122979818APending Publication Date: 2026-10-27高宏 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510456915.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

常规方式是选择石墨、石墨烯、石油焦、煤、煤焦粉和木炭等各种各样的碳粉加入铝合金中,采用熔融搅拌、低温搅拌、低温等离子渗透、3D打印+热处理、熔融+大电流辅助等方式,但效果不佳,因为碳与铝的渗透角度过大,铝水无法浸润碳,碳元素无法真正融入铝合金,现在已有的铝合金都视其中所含的碳为杂质,在铝合金中起破坏铝合金理化性能的作用,碳是尽量排除的元素,碳原子和铝原子无法形成稳定的化合物、络合物或中间合金物或未知的形态存在

Benefits of technology

[0023]试验得出,首先,通过本发明的渗碳剂处理,可以在铝及铝合金中加入碳,并检测出碳含量,但碳含量稀释比例不稳定。其次,加入渗碳剂的铝合金,由照片对比可知碳可明显细化铝合金晶粒,由拉伸试验可知可优化铝合金的抗拉性、拉伸率、抗折性,但具体碳含量对于铝合金的优化效果也不确定。经申请人分析推测,可能是被熔融的电解质浸润过的碳粉颗粒发生了改性具备了能渗透进入铝合金的功能,使改性后的碳原子和铝原子能形成化合物或络合物,或其它未知结构的稳定形式存在,能够使得铝和碳的结合更稳定,使铝合金发生了根本性的改变,上述原因申请人会在后续研究和试验中跟进和验证。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979818A_ABST
    Figure CN122979818A_ABST
Patent Text Reader

Abstract

The present application discloses a method for carburizing aluminum and the obtained aluminum-carbon alloy, characterized in that, in the molten aluminum or aluminum alloy, fluorinated salt and carbon powder are added, stirred and cooled to obtain the carburized aluminum or aluminum alloy. The aluminum alloy produced by the carburizing method has stable physical and chemical properties after melting, and the carbon can obviously refine the aluminum alloy grains, and the tensile strength, tensile rate and bending resistance of the as-cast aluminum alloy are obviously changed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallurgy, specifically relating to a method for carburizing aluminum and the resulting aluminum-carbon alloy. Background Technology

[0002] Electrolytic aluminum is the raw material for producing aluminum materials and aluminum alloys. Aluminum is a metal with low strength and good ductility. Besides the use of pure aluminum, it is alloyed to improve strength or overall performance. Adding one or more alloying elements to aluminum alters its microstructure and properties, making it suitable for various processed materials or cast parts. Commonly added alloying elements include copper, magnesium, zinc, silicon, and more than 40 other elements. Currently, aluminum alloys are classified into nine series, representing alloys with copper, manganese, silicon, magnesium, etc., as the main alloying elements. However, none of these nine series contain carbon.

[0003] Domestic and international companies and research institutions have long attempted to incorporate carbon into aluminum alloys, but without substantial breakthroughs. Conventional methods involve adding various carbon powders such as graphite, graphene, petroleum coke, coal, coal coke powder, and charcoal to the aluminum alloy, employing techniques like melt stirring, low-temperature stirring, low-temperature plasma infiltration, 3D printing combined with heat treatment, and melting combined with high-current assistance. However, these methods have yielded unsatisfactory results because the penetration angle between carbon and aluminum is too large, preventing the molten aluminum from wetting the carbon and ensuring that the carbon element cannot truly integrate into the aluminum alloy. Existing aluminum alloys generally consider the carbon content as an impurity, believing it to damage the alloy's physicochemical properties. Carbon is an element that is largely excluded, as carbon atoms cannot form stable compounds, complexes, intermediate alloys, or exist in unknown forms with aluminum atoms. Therefore, existing carbon-containing aluminum alloys cannot be considered true alloys, exhibiting various defects such as poor shock resistance, poor heat resistance, and poor flexural strength. Furthermore, unlike steel, they cannot retain carbon after melting, preventing it from separating and floating out due to differences in density. To date, they have not been able to be practically applied.

[0004] Patent application number 201110360403.3 discloses a low-temperature surface carburizing method for titanium-aluminum based intermetallic compound materials, including the following steps: (1) surface nano-sizing of the TiAl-based alloy surface using conventional equipment and methods; (2) low-temperature carburizing of the nano-sized TiAl-based alloy at 500℃~800℃ to prepare a carburized layer of 4~9µm thickness on the sample surface. Such treatment only infiltrates a micron-level carbon layer on the material surface and cannot be considered a carbon-containing aluminum alloy. Summary of the Invention

[0005] The purpose of this invention is to provide a method for carburizing aluminum, which can incorporate carbon into aluminum alloys to improve their performance, and also to provide an aluminum-carbon alloy that has better performance than existing aluminum alloys.

[0006] The technical solution of this invention. A method for carburizing metallic aluminum, comprising adding fluoride salts and carbon powder to molten aluminum or aluminum alloy, stirring and then cooling to obtain carburized aluminum or aluminum alloy.

[0007] The fluoride salt is potassium fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, aluminum fluoride, calcium fluoride, fluorosilicate, fluorotitanate, fluoroborate, cryolite, or / and an electrolyte generated during aluminum electrolysis, wherein one or more of these are mixed.

[0008] The fluoride salt is an electrolyte produced by sodium fluoride, aluminum fluoride, cryolite, or / and electrolytic aluminum, wherein one or more of these are mixed.

[0009] The fluoride salt and carbon powder are pre-treated. The fluoride salt is melted and then added to the carbon powder for mixing. After stirring and cooling, the mixture is pulverized and then added to molten aluminum or aluminum alloy.

[0010] The melting temperature of the fluoride salt is 700-1200℃.

[0011] The melting temperature of the aluminum or aluminum alloy is 650-1200℃.

[0012] The carbon is coal, graphite, graphene, petroleum coke, coal coke powder, carbon black, cathode carbon blocks, anode carbon blocks, or / and charcoal, one or a mixture of two or more of these.

[0013] The carbon is coal, graphene, graphite, or / and charcoal, one or a mixture of two or more of these.

[0014] An aluminum-carbon alloy, prepared by the above-described carburizing method in metallic aluminum.

[0015] The aluminum-carbon alloy comprises aluminum and carbon reacted with fluoride salts.

[0016] Beneficial effects: This invention can infiltrate carbon into metallic aluminum and aluminum alloys, improving the performance of aluminum and aluminum alloys. By performing carburizing treatment together with chloride salts, the carbon powder particles containing fluoride salts have the function of penetrating into aluminum alloys and can bond better with aluminum. To this end, the applicant has conducted relevant experiments as follows: 1. Aluminum is recycled from aluminum wires and melted at 750℃ to obtain primary aluminum. The primary aluminum is then cast to obtain tensile test samples, designated as the primary aluminum group. A mixture of cryolite and carbon powder is added to the molten primary aluminum at 750℃ in a weight ratio of 1000:100, stirred thoroughly, and cast to obtain tensile test samples, designated as the primary aluminum carburizing group one. Samples from the primary aluminum carburizing group are then added to the primary aluminum in a weight ratio of 1000:1000, remelted at 750℃, stirred thoroughly, and cast to obtain tensile test samples, designated as the primary aluminum carburizing dilution group one. The mixture of cryolite and carbon powder, in a weight ratio of 100:100, is obtained by melting the cryolite and then adding the carbon powder, with a carbon powder particle size of 120.

[0017] Carbon slag from the electrolytic cell, waste cathode carbon blocks, and anode residues were added to molten primary aluminum at 750℃. The resulting carbon powder, with a particle size of 120, was then thoroughly stirred and cast to obtain tensile test samples, which served as primary aluminum carburizing group two. Samples from the primary aluminum carburizing group were added to primary aluminum at a weight ratio of 1000:1000 and remelted at 750℃. The mixture was then thoroughly stirred and cast to obtain tensile test samples, which served as primary aluminum carburizing dilution group two.

[0018] Tensile tests were conducted on five groups of test specimens according to GB / T 228.1-2021 Metallic materials—Tension testing—Part 1: Test at room temperature. The results are shown in the figures below. Figure 1-5 The test results show that carburized aluminum can significantly improve its tensile strength and upper and lower yield strength. Low-magnification photographs of the original aluminum group, the original aluminum carburized group, and the original aluminum carburized diluted group are shown below. Figure 6-8 Uncarburized aluminum alloys exhibited significantly coarse grains, while carburized aluminum alloys showed significantly fine grains. The aluminum alloys after carburizing, dilution, and recasting also showed significantly fine grains. Samples from the original carburized aluminum group and the original carburized and diluted aluminum group were sent to the Guizhou Provincial Institute of Analysis and Testing for carbon content analysis. The results are shown below. Figure 9 and 12 The carbon content of primary aluminum carburizing group one is 0.052; 0.052; the carbon content of primary aluminum carburizing dilution group one is 0.0075; the carbon content of primary aluminum carburizing group two is 0.025; 0.021; the carbon content of primary aluminum carburizing dilution group two is 0.012; 0.0095.

[0019] 2. Aluminum alloy 350 purchased from Guiyang Huaheng Machinery Manufacturing Co., Ltd. was melted at 750℃ and cast to obtain tensile test samples, which served as the aluminum alloy 350 group. A mixture of cryolite and carbon powder was added to the molten aluminum alloy 350 at a weight ratio of 1000:100, stirred thoroughly, and cast to obtain tensile test samples, which served as the aluminum alloy 350 carburizing group. Samples from the aluminum alloy 350 carburizing group were added to the primary aluminum from Test 1 at a weight ratio of 1000:1000, stirred thoroughly, and cast to obtain tensile test samples, which served as the aluminum alloy 350 carburizing dilution group.

[0020] Tensile tests were conducted on the samples from the aluminum alloy 350 group, the aluminum alloy 350 carburized group, and the aluminum alloy 350 carburized dilution group. The results are shown in the table below. Figure 13-15 The test results show that carburized aluminum alloy 350 can improve both tensile strength and upper and lower yield strength. Samples from the carburized aluminum alloy 350 group and the carburized diluted aluminum alloy 350 group were sent to the Guizhou Provincial Institute of Analysis and Testing for carbon content analysis. The results are shown below. Figure 16 and 17The carbon content of the aluminum alloy 350 carburizing group is 0.018; 0.031, and the carbon content of the aluminum alloy 350 carburizing dilution group is 0.0084; 0.014.

[0021] 3. Recycle aluminum from aluminum alloy doors and windows, melt it to obtain aluminum alloy 6061, cast aluminum alloy 6061 to obtain tensile test samples, as aluminum alloy 6061 group; add carbon powder containing electrolyte to molten aluminum alloy 6061 at a weight ratio of 1000:100, stir thoroughly, cast to obtain tensile test samples, as aluminum alloy 6061 carburizing group; add the aluminum alloy 6061 carburizing group samples to the original aluminum in test 1 at a weight ratio of 1000:1000, remelt, stir thoroughly, cast to obtain tensile test samples, as aluminum alloy 6061 carburizing dilution group.

[0022] Tensile tests were conducted on the aluminum alloy 6061 group, the aluminum alloy 6061 carburized group, and the aluminum alloy 6061 carburized and diluted group. The results are shown in the table below. Figure 18-20 The test results show that carburized aluminum alloy 6061 significantly improves its tensile strength and upper and lower yield strength. Samples from the carburized and diluted carburized aluminum alloy 6061 groups were sent to the Guizhou Provincial Institute of Analysis and Testing for carbon content analysis. The results are shown below. Figure 21 and 22 The carbon content of the carburized aluminum alloy 6061 group is 0.021; 0.037; 0.020, and the carbon content of the carburized and diluted aluminum alloy 6061 group is 0.013; 0.012.

[0023] Experiments revealed that, firstly, carbon can be added to aluminum and aluminum alloys through the carburizing agent treatment of this invention, and the carbon content can be detected, but the carbon dilution ratio is unstable. Secondly, the addition of the carburizing agent to the aluminum alloy, as shown in photographic comparison, indicates that carbon can significantly refine the aluminum alloy grains. Tensile tests show that it can optimize the tensile strength, elongation, and flexural strength of the aluminum alloy, but the specific optimization effect of carbon content on the aluminum alloy is uncertain. The applicant speculates that the carbon powder particles, wetted by the molten electrolyte, may have been modified to possess the ability to penetrate into the aluminum alloy, allowing the modified carbon atoms and aluminum atoms to form compounds or complexes, or other stable forms of unknown structures. This makes the bond between aluminum and carbon more stable, fundamentally altering the aluminum alloy. The applicant will follow up and verify these reasons in subsequent research and experiments. Attached Figure Description

[0024] Figures 1-5 These are the tensile test records for the primary aluminum group, the primary aluminum carburized group 1, the primary aluminum carburized dilution group 1, the primary aluminum carburized group 2, and the primary aluminum carburized dilution group 2. Figures 6-8 These are low-magnification photographs of cross-sections of samples from the primary aluminum group, the primary aluminum carburized group, and the primary aluminum carburized diluted group. Figures 9-12 These are the carbon content test reports for samples from the primary aluminum carburizing group 1, the primary aluminum carburizing dilution group 1, the primary aluminum carburizing group 2, and the primary aluminum carburizing dilution group 2. Figures 13-15 These are the tensile test records for the aluminum alloy 350 group, the aluminum alloy 350 carburized group, and the aluminum alloy 350 carburized dilution group, respectively. Figure 16 This is the carbon content test report for the 350 aluminum alloy carburizing sample. Figure 17 This is a carbon content test report for the 350 aluminum alloy carburizing dilution group sample; Figures 18-20 These are the tensile test records for the aluminum alloy 6061 group, the aluminum alloy 6061 carburized group, and the aluminum alloy 6061 carburized dilution group, respectively. Figure 21 This is the carbon content test report for the carburized aluminum alloy 6061 sample. Figure 22 This is a carbon content test report for the carburized and diluted aluminum alloy 6061 sample. Detailed Implementation

[0025] The present invention will be further described below with reference to embodiments and comparative examples, but these are not intended to limit the present invention. Example

[0026] A method for carburizing aluminum involves adding fluoride salts and carbon powder to molten aluminum or an aluminum alloy, stirring, and then cooling to obtain carburized aluminum or an aluminum alloy.

[0027] The fluoride salt is potassium fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, aluminum fluoride, calcium fluoride, fluorosilicate, fluorotitanate, fluoroborate, cryolite, or / and an electrolyte generated during aluminum electrolysis, wherein one or more of these are mixed.

[0028] The fluoride salt is an electrolyte produced by sodium fluoride, aluminum fluoride, cryolite, or / and electrolytic aluminum, wherein one or more of these are mixed.

[0029] The fluoride salt and carbon powder are pre-treated. The fluoride salt is melted and then added to the carbon powder for mixing. After stirring and cooling, the mixture is pulverized and then added to molten aluminum or aluminum alloy.

[0030] The melting temperature of the fluoride salt is 700-1200℃.

[0031] The melting temperature of the aluminum or aluminum alloy is 650-1200℃.

[0032] The carbon is coal, graphite, graphene, petroleum coke, coal coke powder, carbon black, cathode carbon blocks, anode carbon blocks, or / and charcoal, one or a mixture of two or more of these.

[0033] The carbon is coal, graphene, graphite, or / and charcoal, one or a mixture of two or more of these.

[0034] An aluminum-carbon alloy, prepared by the above-described carburizing method in metallic aluminum.

[0035] The aluminum-carbon alloy comprises aluminum and carbon reacted with fluoride salts.

[0036] The particle size of the toner is 40-300 mesh.

[0037] By weight, carbon accounts for 40%-0.001% of aluminum. Adding carbon to aluminum and aluminum alloys can improve their tensile strength, elongation, and flexural strength, but the specific optimization effect of carbon content on aluminum alloys is currently uncertain. Therefore, when the carbon content in aluminum-carbon alloys is high, they can be used as intermediates for subsequent production of other aluminum alloys. When the carbon content in aluminum-carbon alloys is high, the appropriate carbon content should be selected based on the different contents of aluminum and aluminum alloys to obtain aluminum alloy materials with better performance. For example, in the experiment, adding about 0.01-0.03% carbon to recycled primary aluminum, aluminum alloy 6061, and aluminum alloy 350 can improve the tensile strength and upper and lower yield strength of the aluminum alloys.

[0038] In use, the fluoride salt is heated to a molten state (temperature reaches 700℃~1200℃), and then carbon powder is added to the fluoride salt and stirred, so that the fluoride salt is infiltrated into the carbon powder particles and absorbed by the carbon powder particles. The carbon powder particles that have absorbed the fluoride salt are added to the molten aluminum alloy. At this time, the carbon powder particles containing fluoride salt are modified to have the function of allowing carbon to penetrate into the aluminum alloy, so that aluminum and carbon form stable compounds, complexes, intermediate intermetallic compounds, or other unknown stable forms of substances. The carbon in the carbon-containing aluminum alloy formed will not separate from the aluminum due to the remelting of the aluminum alloy, and the carbon will not float out of the aluminum liquid, causing the recast carbon-containing aluminum alloy to lose its original properties. Example

[0039] When using this product, first melt the fluoride salt and mix it with the carbon powder, then add it to the molten aluminum. Melting the aluminum electrolyte and mixing it with the carbon powder can shorten the reaction time between carbon and aluminum and improve the carburizing effect. By weight, the amount of carbon used is 30%-0.005% of the aluminum. Example

[0040] Potassium fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, aluminum fluoride, or calcium fluoride, one or more of these, are mixed and melted at 750-850℃. Petroleum coke or coal coke powder with a carbon particle size of 140-180 mesh is added, and then added to molten aluminum or aluminum alloy. After stirring and cooling, carburized aluminum or aluminum alloy is obtained. The amount of carbon used is 20%-0.01% of the aluminum by weight. Example

[0041] By weight, 10% fluoride salt and 90% carbon powder are mixed to obtain a carburizing agent. The fluoride salt can be potassium fluoride, lithium fluoride, sodium fluoride, or aluminum fluoride, one or more of which are mixed. The carbon powder can be graphite, petroleum coke, coal coke powder, or coal powder, one or more of which are mixed. The carbon powder particle size is 200 mesh. In use, the fluoride salt is first melted and mixed with the carbon powder, then added to molten aluminum. Alternatively, the fluoride salt and carbon powder can be directly added to molten aluminum. By weight, the amount of carbon is 15% of the aluminum. Example

[0042] By weight, 20% fluoride salt and 80% carbon powder are mixed. The fluoride salt is selected from the electrolyte produced by electrolytic aluminum, and the carbon powder is selected from cathode carbon blocks or anode carbon block waste ground into powder with a particle size of 150 mesh. The mixture is then added to molten aluminum or aluminum alloy, stirred and cooled to obtain carburized aluminum or aluminum alloy. By weight, the amount of carbon used is 10% of the aluminum. Example

[0043] The carbon slag from the overhaul of the electrolytic cell in aluminum electrolysis production, waste cathode carbon blocks, and anode residues are collected, crushed, and floated to obtain carbon powder containing fluoride salts. By weight, its composition is approximately 30% fluoride salts and 70% carbon powder. The carbon powder containing fluoride salts is added to aluminum in a molten state at 800℃. The carbon powder has a particle size of 160 mesh, and by weight, the amount of carbon used is 5% of the aluminum. Example

[0044] By weight, 40% fluoride salt and 60% carbon powder are mixed. The carbon powder is made from coal, graphene, graphite or charcoal. The fluoride salt is selected from fluorosilicate, fluorotitanate or fluoroborate, one or a combination thereof, such as sodium fluorosilicate, potassium fluorosilicate, sodium fluorotitanate, potassium fluoroborate, sodium fluoroborate or potassium fluoroborate, etc. Then it is added to aluminum alloy in molten state at 900℃ and stirred evenly. The aluminum alloy is various aluminum alloys with existing grades. By weight, the amount of carbon is 3% of the aluminum. Example

[0045] By weight, 50% fluoride salt and 50% carbon powder are mixed. The fluoride salt is sodium fluoride, aluminum fluoride or cryolite, and the carbon powder is graphite or charcoal. Then, it is added to aluminum alloy in molten state at 1000℃ and stirred evenly. By weight, the amount of carbon is 1% of the aluminum. Example

[0046] By weight, 60% fluoride salt and 40% carbon powder are mixed, the fluoride salt being cryolite and the carbon powder being graphite, and then added to aluminum alloy in molten state at 1100℃ and stirred evenly. By weight, the amount of carbon used is 0.5% of the aluminum.

[0047] Example 10.

[0048] By weight, 70% fluoride salt and 30% carbon powder are mixed, the fluoride salt being an aluminum electrolyte and the carbon powder being carbon black. This mixture is then added to molten aluminum at 950°C and stirred until homogeneous. By weight, the amount of carbon used is 0.01% of the aluminum.

[0049] Example 11.

[0050] By weight, 80% fluoride salt and 10% carbon powder are mixed. The fluoride salt is a mixture of potassium fluoride and sodium fluoride. The carbon powder is petroleum coke with a particle size of 200 mesh. Then, it is added to molten aluminum at 750℃ and stirred evenly. By weight, the amount of carbon is 0.05% of the aluminum.

[0051] Example 12.

[0052] By weight, 90% fluoride salt and 10% carbon powder are mixed. The fluoride salt is a mixture of potassium fluoride and sodium fluoride. The carbon powder is petroleum coke with a particle size of 200 mesh. Then, it is added to molten aluminum at 750°C and stirred evenly. By weight, the amount of carbon is 0.02% of the aluminum.

Claims

1. A method for carburizing aluminum, characterized in that, Fluoride salts and carbon powder are added to molten aluminum or aluminum alloys, and the mixture is stirred and then cooled to obtain carburized aluminum or aluminum alloys.

2. The method for carburizing metallic aluminum according to claim 1, characterized in that, The fluoride salt is potassium fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, aluminum fluoride, calcium fluoride, fluorosilicate, fluorotitanate, fluoroborate, cryolite, or / and an electrolyte generated during aluminum electrolysis, wherein one or more of these are mixed.

3. The method for carburizing metallic aluminum according to claim 2, characterized in that, The fluoride salt is an electrolyte produced by sodium fluoride, aluminum fluoride, cryolite, or / and electrolytic aluminum, wherein one or more of these are mixed.

4. The method for carburizing metallic aluminum according to claim 1, characterized in that, The fluoride salt and carbon powder are pre-treated. The fluoride salt is melted and then added to the carbon powder for mixing. After stirring and cooling, the mixture is pulverized and then added to molten aluminum or aluminum alloy.

5. The method for carburizing metallic aluminum according to claim 4, characterized in that, The melting temperature of the fluoride salt is 700-1200℃.

6. The method for carburizing metallic aluminum according to claim 1, characterized in that, The melting temperature of the aluminum or aluminum alloy is 650-1200℃.

7. The method for carburizing metallic aluminum according to claim 1, characterized in that, The carbon is coal, graphite, graphene, petroleum coke, coal coke powder, carbon black, cathode carbon blocks, anode carbon blocks, or / and charcoal, one or a mixture of two or more of these.

8. The method for carburizing metallic aluminum according to claim 7, characterized in that, The carbon is coal, graphene, graphite, or / and charcoal, one or a mixture of two or more of these.

9. An aluminum-carbon alloy, characterized in that, It is prepared by carburizing aluminum according to any one of claims 1-8.

10. The aluminum-carbon alloy according to claim 9, characterized in that, The aluminum-carbon alloy comprises aluminum and carbon reacted with fluoride salts.

Citation Information

Patent Citations

  • Low-temperature surface carburization method for titanium-aluminum-based intermetallic compound material

    CN102409282A